The last battle - Lewis, C.S. (Lahore ILQA Publications, 2015)
Having seen nearly 2500 years of its existance, the Narnian world is in turmoil. The ape Shift has introduced a fake Aslan who is simply a donkey in a lion s skin. Most of Narnians believe Shift and do what he says. When Tirian, the ruling Narnian king, and his fistful faithfuls accuse Fist of lying, Tirian is captured. What will the king do? Will Aslan come to his rescue? Will he send the earthlings to help Narnians? Will Narnia last? (3z(BThe Last Battle(3y (Bis the 7th and last novel in C. S. Lewis s great (3z(BThe Chronicles of Narnia(3y(B.s
A classic of children s fantasy literature, (3z(BThe Chronicles of Narnia(3y (Bis a series of seven stand-alone books. It is one of the most popular children series ever written. It has been translated in more than 40 languages and sold over 100 million copies around the world.s
Keywords: Adventure Books, Adventure Books, Classic Books & Novels, Contemporary & General Fiction, Children Fantasy & Sci-Fi, Children Fiction & Stories, Classic Books, Novels & Novelettes